ANALISIS PENILAIAN KELAS DAN PROGRAM TINDAK LANJUT PEMBELAJARAN PENDIDIKAN AGAMA ISLAM DAN BUDHI PEKERTI SISWA KELAS VII SMPN 15 TANGERANG - basyit, abdul; Mukhtarom, Asrori; Anwar, Khoirul; Husein, Muh Turizal; rawi, Nah (Rausyan Fikr : Jurnal Pemikiran dan Pencerahan, 2023)
ABSTRACTThe problem of the research is the Class Assessment Analysis and the Follow-up Program on Islamic Religious Education Learning Class VII at SMP Negeri 15 Tangerang City. This study aims to analyze class assessment and follow-up programs for Islamic religious education subjects for class VII. The research method used is descriptive qualitative research. The procedure of this research is through interviews with observations on the class assessment process and follow-up programs on learning Islamic religious education in class VII SMP Negeri 15 Tangerang City. The results of this study show: 1) Class assessment of Islamic Religious Education learning in Class VII SMP Negeri 15 Tangerang City according to the standardization of formal education in general. 2) The follow-up program on learning Islamic Religious Education in Class VII SMP Negeri 15 Tangerang City has not been implemented only